2019
DOI: 10.1186/s12864-019-6062-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Phytoplasma solani’ interferes with the distribution and uptake of iron in tomato

Abstract: Background ‘Candidatus Phytoplasma solani’ is endemic in Europe and infects a wide range of weeds and cultivated plants. Phytoplasmas are prokaryotic plant pathogens that colonize the sieve elements of their host plant, causing severe alterations in phloem function and impairment of assimilate translocation. Typical symptoms of infected plants include yellowing of leaves or shoots, leaf curling, and general stunting, but the molecular mechanisms underlying most of the reported changes remain la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 110 publications
(114 reference statements)
3
31
0
1
Order By: Relevance
“…Solyc01g010480 (Log 2 Fc = −2.2; tomato K+ channel KAT1) was demonstrated to be highly upregulated in low K tolerant tomato genotypes upon potassium deficiency ( Zhao et al, 2018 ). Solyc01g102610.3.1 (Log2Fc = −3.60; tomato FRO6) is involved in nutrient transport in phloem and was observed to be downregulated under Phytoplasma solani infection of tomato ( Buoso et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Solyc01g010480 (Log 2 Fc = −2.2; tomato K+ channel KAT1) was demonstrated to be highly upregulated in low K tolerant tomato genotypes upon potassium deficiency ( Zhao et al, 2018 ). Solyc01g102610.3.1 (Log2Fc = −3.60; tomato FRO6) is involved in nutrient transport in phloem and was observed to be downregulated under Phytoplasma solani infection of tomato ( Buoso et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…As one of the first visible symptoms of disease progression, leaf chlorosis might be exacerbated by poor soil fertility. In this context, Buoso et al [70] reported that iron deficiency in phytoplasma-infected plants had negative impacts on chlorophyll pigment and young leaf chlorosis in tomato plants. The sesame's lower leaf greenness index (i.e., chlorophyll content) in our study related to the severe damage of the thylakoid stacks, structural and functional destruction of the grana and stroma lamellae of chloroplasts (Figure 9), and increased numbers of starch granules in the infected plant's leaves [23].…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant differences in Fe content of normal and abnormal plants. Buoso et al (2019) observed that phytoplasma infection accumulate Fe from the phloem, converting the phloem into a sink tissue for Fe causing Fe starvation of plant.…”
Section: Effect Of Phytoplasma Infection On Chemical Compositionmentioning
confidence: 99%